1990
DOI: 10.1172/jci114695
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the role of antibody-dependent cellular cytotoxic antibody activity in murine neonatal herpes simplex virus infection with antibodies to synthetic peptides of glycoprotein D and monoclonal antibodies to glycoprotein B.

Abstract: The role of antibody in neonatal herpes simplex virus (HSV) infection remains controversial. A battery of well-characterized monoclonal antibodies to HSV glycoprotein B (gB), and polyclonal antibodies against synthetic peptides of predicted epitopes of HSV glycoprotein D (gD) were used to determine in vitro functional activity and association with protection against lethal infection in a murine model of neonatal HSV disease. Antiviral neutralization activity of HSV was not associated with antibody-dependent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…In fact, we have observed that mice coimmunized with ICP27 peptide ϩ gD 4 -23 are markedly more resistant to HSV challenge than are ICP27 peptide-immunized mice. However, the recipients of gD 4 -23 also generate CD4 ϩ and Ab response to HSV, which as shown previously also protect against challenge (29). The issue of assessing the in vivo significance of high avidity CTL requires evaluation in circumstances which avoid such complications.…”
Section: Figurementioning
confidence: 89%
“…In fact, we have observed that mice coimmunized with ICP27 peptide ϩ gD 4 -23 are markedly more resistant to HSV challenge than are ICP27 peptide-immunized mice. However, the recipients of gD 4 -23 also generate CD4 ϩ and Ab response to HSV, which as shown previously also protect against challenge (29). The issue of assessing the in vivo significance of high avidity CTL requires evaluation in circumstances which avoid such complications.…”
Section: Figurementioning
confidence: 89%
“…Monoclonal antibodies (MAbs), which consist of a pure antibody protein, have high antibody titres and some show very potent antiviral activity (Grose et al, 1983;Forghani et al, 1984;Keller et al, 1984;Kohl et al, 1990). All these MAbs are of rodent origin and are recognized as foreign substances by the human immune system (Khazaeli et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…F cR-bearing cells armed with Abs can kill virus-infected cells by Ab-dependent cellular cytotoxicity (ADCC), 3 an immune mechanism known to occur in vitro and in vivo (1)(2)(3). Passive transfer of Abs with in vitro ADCC activity against HSVinfected cells, for example, can protect complement-deficient mice against lethal challenge with HSV, despite the inability of the Abs to neutralize the virus (4).…”
mentioning
confidence: 99%